5問 足し算 分数足し算 数学・算数の教材公開ページ

20 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) 1 6 +

1

3 = (2)

1 4 +

1 6 =

(3) 7 4 +

5

3 = (4)

5 2 +

1 4 =

(5) 5 4 +

1 6 =

(2)

(1) 16 + 1 3 =

1

2

(2)

1 4 +

1 6 =

5

12

(3) 74 + 5 3 =

41

12

(4)

5 2 +

1 4 =

11

4

(5) 54 + 1 6 =

17

12

(3)

(1) 5 3 +

1

2 = (2)

5 2 +

3 4 =

(3) 1 2 +

1

3 = (4)

4 3 +

5 2 =

(5) 2 3 +

1 6 =

(4)

(1) 53 + 1 2 =

13

6

(2)

5 2 +

3 4 =

13

4

(3) 12 + 1 3 =

5

6

(4)

4 3 +

5 2 =

23

6

(5) 23 + 1 6 =

5

6

(5)

(1) 1 6 +

3

2 = (2)

5 2 +

4 3 =

(3) 4 5 +

3

4 = (4)

5 3 +

1 6 =

(5) 2 3 +

1 6 =

(6)

(1) 16 + 3 2 =

5

3

(2)

5 2 +

4 3 =

23

6

(3) 45 + 3 4 =

31

20

(4)

5 3 +

1 6 =

11

6

(5) 23 + 1 6 =

5

6

(7)

(1) 2 3 +

5

4 = (2)

2 3 +

5 6 =

(3) 1 3 +

5

6 = (4)

3 2 +

5 4 =

(5) 7 4 +

1 6 =

(8)

(1) 23 + 5 4 =

23

12

(2)

2 3 +

5 6 =

3

2

(3) 13 + 5 6 =

7

6

(4)

3 2 +

5 4 =

11

4

(5) 74 + 1 6 =

23

12

(9)

(1) 1 2 +

5

6 = (2)

3 2 +

5 6 =

(3) 1 4 +

4

5 = (4)

2 3 +

1 6 =

(5) 1 6 +

1 3 =

(10)

(1) 12 + 5 6 =

4

3

(2)

3 2 +

5 6 =

7

3

(3) 14 + 4 5 =

21

20

(4)

2 3 +

1 6 =

5

6

(5) 16 + 1 3 =

1

2

(11)

(1) 2 3 +

5

6 = (2)

3 5 +

3 4 =

(3) 1 3 +

5

6 = (4)

7 4 +

5 6 =

(5) 1 6 +

1 4 =

(12)

(1) 23 + 5 6 =

3

2

(2)

3 5 +

3 4 =

27

20

(3) 13 + 5 6 =

7

6

(4)

7 4 +

5 6 =

31

12

(5) 16 + 1 4 =

5

12

(13)

(1) 4 3 +

5

6 = (2)

3 2 +

2 3 =

(3) 7 4 +

1

3 = (4)

1 6 +

5 2 =

(5) 2 5 +

5 3 =

(14)

(1) 43 + 5 6 =

13

6

(2)

3 2 +

2 3 =

13

6

(3) 74 + 1 3 =

25

12

(4)

1 6 +

5 2 =

8

3

(5) 25 + 5 3 =

31

15

(15)

(1) 1 3 +

1

6 = (2)

4 5 +

1 3 =

(3) 5 4 +

3

2 = (4)

4 3 +

5 4 =

(5) 3 2 +

3 4 =

(16)

(1) 13 + 1 6 =

1

2

(2)

4 5 +

1 3 =

17

15

(3) 54 + 3 2 =

11

4

(4)

4 3 +

5 4 =

31

12

(5) 32 + 3 4 =

9

4

(17)

(1) 1 6 +

4

3 = (2)

5 3 +

5 4 =

(3) 1 3 +

1

6 = (4)

1 2 +

4 5 =

(5) 5 4 +

4 3 =

(18)

(1) 16 + 4 3 =

3

2

(2)

5 3 +

5 4 =

35

12

(3) 13 + 1 6 =

1

2

(4)

1 2 +

4 5 =

13

10

(5) 54 + 4 3 =

31

12

(19)

(1) 7 4 +

1

2 = (2)

5 6 +

3 2 =

(3) 5 4 +

1

2 = (4)

7 4 +

1 5 =

(5) 3 4 +

1 2 =

(20)

(1) 74 + 1 2 =

9

4

(2)

5 6 +

3 2 =

7

3

(3) 54 + 1 2 =

7

4

(4)

7 4 +

1 5 =

39

20

(5) 34 + 1 2 =

5

4

Updating...

参照

Updating...

関連した話題 :